Hubungan Intensitas Kebisingan Dengan Gangguan Psikologis Pekerja Departemen Laundry Bagian Washing PT. X Semarang - Ferri Kristiyanto; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2014)
The use of technology in the workplace in terms of facilities and infrastructure will generate noise or unwanted sound that will cause health problems in workers that occupational diseases. The impact of noise on health that occurs in labor could be psychological disorders such as convenience disorders, stress, insomnia, easy emotion, and impaired concentration which can cause accidents. The purpose of this study was to analyze the relationship of noise intensity with psychological disorders laundry department worker washing part of PT. X Semarang. The design of the study is a cross sectional method with the type of explanatory research and observational approach. The population in this study was the morning shift workers who work at the washing amounted to 110 people, the samples taken were 76 people using purposive sampling technique. The sources was data obtained from the measurement noise and interviews. Based on the research showed that workers experience psychological disorders. The statistical test used the Spearman rank correlation test at α 5% (0,05) showed r = 0,894 with p value = 0,000. It was concluded that there way a relationship with the noise intensity psychological disturbances parts washing laundry department worker PT. X Semarang